2022
DOI: 10.1037/ppm0000405
|View full text |Cite
|
Sign up to set email alerts
|

Parent–child communication about gender and race through the films Black Panther and Wonder Woman: The roles of parental mediation and media literacy.

Abstract: This research explores parent-child communication about gender and race through popular media. Specifically, this study examined how White and Black parents (N = 185) discussed the critically acclaimed films Black Panther and Wonder Woman with their children (aged 7-12 years). Findings reveal significant relationships between parents' media literacy skills, mediation styles, and parent-child conversations about race and gender through these popular superhero films. Higher levels of media literacy and active me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The diversity on Strictly Come Dancing is a good thing. Prior research has shown that diversity on popular media can spark much-needed conversations about diversity and bias in real life (Behm-Morawitz et al, 2022). After watching Strictly Come Dancing, Cathy Reay (Reay, 2022) wrote about how enraptured and transfixed her children were to see someone like them (i.e., someone with dwarfism) represented in a positive way on a dancing show.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity on Strictly Come Dancing is a good thing. Prior research has shown that diversity on popular media can spark much-needed conversations about diversity and bias in real life (Behm-Morawitz et al, 2022). After watching Strictly Come Dancing, Cathy Reay (Reay, 2022) wrote about how enraptured and transfixed her children were to see someone like them (i.e., someone with dwarfism) represented in a positive way on a dancing show.…”
Section: Discussionmentioning
confidence: 99%
“…These efforts ultimately contribute to the formation of positive Internet usage habits and the avoidance of problematic online behaviors in adolescents. The ecological techno-subsystem represents a subsystem within the broader ecological system of child development, reflecting the influence of electronic device usage in the family, school, and community on children's development [60].Active mediation style, combined with higher levels of media literacy, was associated with a higher likelihood of parents engaging in conversations with their children [61]. The family functions as a direct microenvironment for adolescent Internet usage, where parental attitudes towards the Internet and mediation towards online behavior directly impact adolescents' Internet adaptation.…”
Section: The Direct Effect Of Active Parental Mediationmentioning
confidence: 99%